Leaders, Followers and Depth of Connection - Mark Avery; Mindaugas Stankunas (ACHSM, 2024)
Leading and leadership are fundamentally about relationships between a leader and those who want to follow to achieve directions through an influencing relationship [1]. Critical relationship issues involve trust, communication and mutual respect. In healthcare, how these issues are nurtured and managed enhances teamwork, quality, productivity and impact or success of organisation and systems. A key aspect of the leadership process is for leaders and followers to engage effectively and constructively to achieve the articulated goals and objectives set out by the leader(s). Various leadership styles articulate the mechanisms and ways of leaders and followers connecting. An interesting way of looking at how a leader might relate to a team or group is to consider social identity theory.......